Evaluating the effects on pore pressure decrease from leakage in deep excavations when accounting for geological model uncertainty - Axéen, Sofie (My University, 2024)
Increased population and urbanization have led to challenges for many cities, as available land becomes increasingly limited. This has resulted in an increased interest in building underground facilities. During the construction of these facilities, there is a risk of groundwater leakage which can result in lowering of groundwater levels with subsequent ground subsidence and damage to buildings, infrastructure and other installations. It is therefore important to have a solid understanding and knowledge of the stratigraphy, the hydrogeological properties and thus potential flow paths for water within the building area. In Sweden, it is common to have thin sand layers embedded in clay layers that were formed during the end of the last ice age due to varying sea levels. These local and thin sand layers tend to be overlooked in groundwater modelling when attempting to predict pore pressure changes and settlement calculations. The aim of this work has therefore been to investigate how the inclusion of these sand layers affects forecasts of pore pressure changes as a result of leakage due to deep excavation. This has been done through numerical modelling based on two different geological conceptualisations, where the first model assumes that the clay is homogeneous and the second includes these sand layers. The flow models have been developed in MODFLOW and applied to a hypothetical shaft located at Korsvägen, Gothenburg. The results show significant differences between the models, where the inclusion of sand layers results in faster pore pressure decrease in the clay while the pressure level in the lower aquifer increases. In addition, local differences were observed where the influence of the sand layers can both result in increasing and decreasing pore pressure, depending on their position and possible connectivity to the upper or lower aquifer. In summary, the results underline the importance of including these types of geological uncertainties, as they have an impact on pore pressure changes. Failure to consider these factors can potentially lead to underestimation of settlement risks and thus damage to buildings and other installations.
Keywords: groundwater modelling; uncertainties; MODFLOW; groundwater drawdown; pore pressure decrease